(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Migration and distribution of lead in the water–bottom sediment system of the Hrazdan River has been investigated. In order to evaluate migration magnitude of metals and the influence of different parameters on it, liner dependence between partition coefficient of metals and different parameters of environment for 2012–2013 period has been studied.